Designers for/and/with manufacturing: design-driven solutions for an updated dialogue between young creative talents and the textile-knitwear industry - Conti, Giovanni Maria (2025)
The article presents the research Context, built on the network of relationships with textile and knitwear companies established by the research team KnitDesign Lab and Imagis lab. A first investigation on the existing relationships showed that they empowered the update of educational practices but also evidenced a great gap between the university and entrepreneurial realities in understanding each other’s practices, skills, objectives. Combining the expertise in the textile-knitwear area of KnitDesign Lab with the one in communication of Imagis lab, the research project investigated the present needs and the future visions of young design talents and manufacturers and developed solutions to make them converge towards a common meeting point, with the aim to lay valid foundations for a constructive dialogue between the two opposite poles. The research is here presented with its methodology, structure and detailed results.